Blood Krebs von den Lungen-6 levels predict treatment response to antifibrotic therapy in patients with idiopathic pulmonary fibrosis - Myeong Geun Choi; Sun Mi Choi; Jae Ha Lee; Joong-Yub Kim; Jin Woo Song (Respiratory Research, 2022)
Abstract Background Antifibrotic therapy can slow disease progression (DP) in patients with idiopathic pulmonary fibrosis (IPF). However, the prognostic biomarkers for DP in patients with IPF receiving antifibrotic therapy have not been identified. Therefore, we aimed to evaluate the prognostic efficacy of serum Krebs von den Lungen-6 (KL-6) for DP in patients with IPF receiving antifibrotic therapy. Methods The clinical data of 188 patients with IPF who initiated antifibrotic therapy at three tertiary hospitals was retrospectively analyzed. DP was defined as a relative decline in forced vital capacity (FVC) ≥ 10%, diffusing capacity for carbon monoxide ≥ 15%, acute exacerbation, or deaths during 6 months after antifibrotic therapy. Results The mean age of patients was 68.9 years, 77.7% were male, and DP occurred in 43 patients (22.9%) during follow-up (median, 7.6 months; interquartile range, 6.2–9.8 months). There was no difference in baseline KL-6 levels between the DP and no-DP groups; however, among patients with high baseline KL-6 levels (≥ 500 U/mL), changes in KL-6 levels over 1 month were higher in the DP group than those in the non-DP group, and higher relative changes in KL-6 over 1 month were independently associated with DP (odds ratio, 1.043; 95% confidence interval 1.005–1.084) in the multivariable logistic analysis adjusted for age and FVC. In the receiver operating characteristic curve analysis, the 1-month change in KL-6 was also useful for predicting DP (area under the curve = 0.707; P < 0.012). Conclusions Our data suggest that the relative change in KL-6 over 1 month might be useful for predicting DP in patients with IPF receiving antifibrotic therapy when baseline KL6 is high.